2022
DOI: 10.1057/s41308-022-00172-w
|View full text |Cite
|
Sign up to set email alerts
|

A Disaster Under-(Re)Insurance Puzzle: Home Bias in Disaster Risk-Bearing

Abstract: We examine disaster reinsurance from the perspective of international risk-sharing. We find that losses from disasters are shared internationally to a generally very limited extent, unlike what the theory of international risk-sharing suggests. We propose a new dataset of cross-border reinsurance payments for 93 disasters of 44 economies in 1982–2017. Combining these balance of payments data with industry data, we find that the lack of disaster risk-sharing through international reinsurance results from low pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Countries might also accumulate foreign exchange from international (re)insurance payments. Ito and McCauley (2019) show empirical evidence that the international reinsurance share is positively associated with IR. They also found that losses from disasters are only shared internationally to a very limited extent across countries; the average portion of economic damage offset by reinsurance is less than 5%.…”
Section: Tablementioning
confidence: 95%
“…Countries might also accumulate foreign exchange from international (re)insurance payments. Ito and McCauley (2019) show empirical evidence that the international reinsurance share is positively associated with IR. They also found that losses from disasters are only shared internationally to a very limited extent across countries; the average portion of economic damage offset by reinsurance is less than 5%.…”
Section: Tablementioning
confidence: 95%
“…In New Zealand, insurance coverage is over 95% for residential buildings, and international reinsurance covered half of the losses from disasters in New Zealand (Reserve Bank of New Zealand, 2011). Japan, however, has a much lower insurance coverage with a relatively low rate of international reinsurance (Ito and McCauley, 2019;Nguyen and Noy, 2020). Quake-affected countries also have to consider a tradeoff between IR holding and its opportunity costs.…”
Section: Related Recent Research Bymentioning
confidence: 99%
“…The insured loss was about US$35 to US$40 billion, however, the share of international risk sharing was not high in Japan. In particular, international reinsurance only covered about 4% of the overall residential loss (Ito and McCauley, 2019). The main public earthquake insurance system in Japan is run by the Ministry of Finance, and it pools and redistributes the risk.…”
Section: It Countries Inmentioning
confidence: 99%